Pendidikan Karakter pada Kegiatan Pentas Seni bagi Anak Usia Sekolah Dasar - Kurniati, Fatia; Erawati, Yahyar; Dwi Tamara, Putri (JPKS (Jurnal Pendidikan dan Kajian Seni), 2025)
The purpose of this study was to reveal the existence of character education values in the art performances held at SD Negeri 182 Pekanbaru. This study used a qualitative research method. Data collection techniques used observation, documentation studies, and interviews. The results of the study showed the existence of character education values contained in art performance activities including discipline, hard work, creativity, cooperation, independence, love of the homeland, Based on the findings of character education values contained in art performance activities, this activity is able to be a medium for developing character education values and implementing character education values for elementary school children